Analisis Teoretis Pengaruh Penggunaan Bahasa Ibu terhadap Kemampuan Literasi Awal Siswa Kelas Rendah - Dhevan Andriano; Salwa Durratunnisa; Silvina Noviyanti; Aisyah Putri Kamalia; Risa Bela Najiah (STKIP Subang, 2026)
This study provides a theoretical examination of the vital role of the mother tongue in supporting early literacy competence among lower-grade elementary students. In the era of globalization, the position of local languages is often seen as contradictory to the mastery of the national language. However, through an indepth analysis based on the Common Underlying Proficiency theory, it is found that the first language is a cognitive asset that facilitates the effective transfer of conceptual understanding. The use of the mother tongue functions as scaffolding that reduces students' mental burden when identifying letter symbols and word meanings, while simultaneously creating an emotionally supportive learning atmosphere. The findings emphasize that although linguistic interference is inevitable, the integrated use of local languages can accelerate reading fluency and strengthen the synergy between home and school education. Keyword : Mother Tongue, Early Literacy, Cognitive Transfer, Scaffolding, LowerGrade Students.